Asociación entre variables sociodemográficas, clínicas y calidad de vida con el apoyo social percibido en pacientes colombianos con cáncer - Luis Fernando Fontibón; Lorena Acosta Hernández; Juliet Valdelamar Jiménez; Adriana Valdelamar Jiménez; Ricardo Sánchez Pedraza (Avances en Psicología Latinoamericana, 2015)
Introduction: Previous studies have found a relationship between quality of life related to health and perceived social support (PSS). Methods: Cross-sectional, analytical study identifying association between sociodemographic, clinical and quality of life variables with the PSS in patients with different types of cancer. One hundred and nineteen patients were evaluated by the questionnaire Medical Outcomes Study Social Support Survey (MOS-SSS) and the Functional Assessment of Cancer Therapy – General (FACT-G) by direct or telephone interview. Data analysis included correlation pattern identification and linear regression. Results: No significant differences between the MOS and categorical variables sex, socioeconomic and marital status were found. Regarding the regression analysis, significant coefficients were found for the variables functional well-being and social well-being (dimensions of the FACT-G) and breast cancer. Comorbidity is associated with higher scores on the MOS scale, as are the dimensions of the FACT-G scale. Conclusion: The PSS interacts positively with the construct of quality of life in cancer patients.